2017
DOI: 10.4292/wjgpt.v8.i2.137
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-free treatments in patients with hepatitis C genotype 1-4 infections in a real-world setting

Abstract: AIMTo investigated the real-world effectiveness and safety of various regimens of interferon-free treatments in patients infected with hepatitis C virus (HCV).METHODSWe performed an observational study to analyze different antiviral treatments administered to 462 HCV-infected patients, of which 56.7% had liver cirrhosis. HCV RNA after 4 wk of treatment and at 12 wk after treatment sustained virologic response (SVR) as well as serious adverse events (SAEs) was analyzed first for the whole cohort and then separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…1 ). Overall, SVR rates for SOF/DCV ± RBV and SOF/SIM ± RBV during 12 weeks ranged from 83 to 98% [ 16 , 17 ] and from 75 to 96% [ 18 29 ], respectively. SVR rates were lower in presence of cirrhosis compared to non-cirrhotic patients (87% vs 98% with SOF/DCV [ 17 ] and 81% vs 91% with SOF/SIM [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Overall, SVR rates for SOF/DCV ± RBV and SOF/SIM ± RBV during 12 weeks ranged from 83 to 98% [ 16 , 17 ] and from 75 to 96% [ 18 29 ], respectively. SVR rates were lower in presence of cirrhosis compared to non-cirrhotic patients (87% vs 98% with SOF/DCV [ 17 ] and 81% vs 91% with SOF/SIM [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, when stratified by eras, the higher waitlist mortality was noted only in the pre‐DAA era and not in the post‐DAA era. This observation is likely attributable to the advent of DAA therapies and corresponds to the relationship between increased success of SVR with DAA therapy and the correlation between SVR and improved mortality for chronic HCV patients …”
Section: Discussionmentioning
confidence: 99%
“…Although protease inhibitors such as boceprevir and telaprevir improved overall SVR rates, use of these medications was limited due to drug‐drug interactions and direct drug toxicity . Sofosbuvir, a second‐generation DAA, targets NS5B and was approved by the FDA in December 2013, and initial clinical trials showed 90% of treatment naïve patients achieved SVR when combined with interferon and ribavirin among patients with genotype 1, and 93%‐100% over genotypes 1‐4 when sofosbuvir was combined with protease inhibitors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower liver stiffness (assessed during treatment at week 4, and after treatment at week 12) was associated with the achievement of sustained virological response in a large observational study (that included 462 patients treated with interferonfree regimen for chronic hepatitis C with viral genotype 1-4) [53].…”
Section: The Liver Stiffness After Treatmentmentioning
confidence: 99%